EFFICIENCY OF PLANT GROWTH PROMOTING RHIZOBACTERIA (PGPR) IN SUGARCANE - Antonio Morgado González; David Espinosa Victoria; Fernando C. Gómez Merino (Terra Latinoamericana, 2015)
Plant growth promoting rhizobacteria (PGPR) are an alternative for promoting sugarcane (Saccharum spp.) development. Growth promotion was evaluated in sugarcane vitroplants inoculated separately with twenty-four strains of seven different bacterial species. Total indole synthesis and phosphate solubilization activity were determined in each strain. The experimental unit was one 5 L pot filled with a sterile mixture of farm soil-agrolite and one plant. The experimental design was completely random. Inoculation consisted of 1.0 mL of bacterial suspension (1 × 107 CFU). Plant height, stem diameter, number of shoots, leaf area and dry matter of shoot and root were determined every two weeks. The Ochrobactrum anthropi strains N208 and IMP311 and Pseudomonas luteola IMPCA244 had the highest production of total indoles (116.69, 115.70 and 117.34 µg mL-1, respectively). The Stenotrophomonas maltophilia strains CA158 and 79 exhibited the highest values of phosphate solubilization (222.43 and 216.38 µg mL-1, respectively). In general, plant height increased 27.75%, stem diameter 30.75%, number of tillers 38.5%, leaf area 49%, aerial dry matter 59.75% and root dry matter 59.5%. P. luteola, P. f luorescens, O. anthropi and S. maltophilia exhibited the highest values of the leaf area index, net assimilation, and relative and absolute growth rates. P. luteola IMPCA244, O. anthropi IMP311, Aeromonas salmonicida N264, Burkholderia cepacia N172, P. f luorescens N50 and S. maltophilia 79 promoted the highest values in different response variables throughout the study. Before using these strains as sugarcane biofertilizer, additional studies are required.